2016
DOI: 10.1186/s12891-016-1235-0
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic stemless shoulder arthroplasty and related outcomes: a systematic review

Abstract: BackgroundThe latest generation of shoulder arthroplasty includes canal-sparing respectively stemless designs that have been developed to allow restoration of the glenohumeral center of rotation independently from the shaft, and to avoid stem-related complications. The stemless prosthesis design has also recently been introduced for use in reverse arthroplasty systems.MethodsWe systematically reviewed the literature for studies of currently available canal-sparing respectively stemless shoulder arthroplasty sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 31 publications
4
53
0
Order By: Relevance
“…Regarding these data, the TESS system allows a reliable restoration of the individual joint geometry. This might explain the relatively good clinical outcome of the TESS prosthesis described in our series as well as in previous studies with follow-up times ranging from 6 to 45 mo[ 26 - 28 , 32 - 34 ].…”
Section: Discussionsupporting
confidence: 84%
“…Regarding these data, the TESS system allows a reliable restoration of the individual joint geometry. This might explain the relatively good clinical outcome of the TESS prosthesis described in our series as well as in previous studies with follow-up times ranging from 6 to 45 mo[ 26 - 28 , 32 - 34 ].…”
Section: Discussionsupporting
confidence: 84%
“…The study showed better forward elevation in TSA compared with HA, whereas ER was similar. These results are comparable with stemless TSA reported by Hawi et al 19 in a systematic review of 11 studies and 929 patients with a mean follow-up of 26 months. Our range of motion results compare favorably with stemmed, stemless, and onlay resurfacing procedures—a benefit that is of particular interest to our relatively young patient population (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…TSA has shown to be effective in reducing pain and improving function in numerous studies;5, 19, 23, 35, 41 however, there is a paucity in the literature comparing TSA outcomes for concentric and eccentric glenoids. To the best of our knowledge, no glenoid stage–specific investigations have been reported using stemless or onlay resurfacing implants.…”
Section: Discussionmentioning
confidence: 99%
“…Few outcome studies on stemless TSA are available. A recent review of 11 observational studies (published 2010-2016), incorporating a total of 929 patients, reported comparable short-and midterm functional outcomes between stemmed and stemless shoulder prosthesis [1]. Otherwise, there are few well-conducted and adequately powered clinical studies.…”
Section: Introductionmentioning
confidence: 99%